Tìm hiểu thêm về biểu tượng nghệ thuật thơ Đinh Hùng - Trần, Văn Ban (Trường Đại học Đà Lạt, 2012)
Dinh Hung is one of the representable poets of new poetry movement, but works that he left less to the readers find, even the academia and critics are too.